Kaidah Hukum Putusan MA Nomor 3549 K/Pdt/2023: Klausul Non Kompetisi dalam Perjanjian Kerja Bukan Pelanggaran HAM - Masagus Hexal Rizkian; Muhammad Zayyaan Nasco; Achmad Muflihuts Tsaqif; Dwi Desi Yayi Tarina (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze and examine the general provisions that serve as the foundation of contract law in Indonesia. Contracts represent one of the most frequent sources of legal obligations in societal relations, making a thorough understanding of their general rules crucial. The research method employed is normative legal research, utilizing both statutory and conceptual approaches. The primary focus of this study includes the legal requirements for a valid contract as stipulated in Article 1320 of the Indonesian Civil Code (KUHPerdata), the principles of contract law such as consensualism, legal certainty (pacta sunt servanda), and good faith, as well as the forms of breach of contract (wanprestasi) and their legal consequences. The results indicate that legal certainty and protection for contracting parties heavily depend on compliance with these general provisions from the pre-contractual stage through to the execution of the contract. Disregarding these general provisions can result in the voiding of the contract or claims for damages.